2017
DOI: 10.1172/jci90678
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-mediated inhibition of serotonin signaling controls the affective component of inflammatory pain

Abstract: Pain is fundamentally unpleasant and induces a negative affective state. The affective component of pain is mediated by circuits that are distinct from those mediating the sensory-discriminative component. Here, we have investigated the role of prostaglandins in the affective dimension of pain using a rodent pain assay based on conditioned place aversion to formalin injection, an inflammatory noxious stimulus. We found that place aversion induced by inflammatory pain depends on prostaglandin E-2 that is synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
(34 reference statements)
1
14
1
3
Order By: Relevance
“…Numerous studies using chemogenetic approaches were conducted to perceive the functions of serotonergic neurons and their projections. In such experiments mice of the Sert-Cre line are injected with adeno-associated viruses containing the sequence hM4Di or hM3Dq (AAV-hSyn-DIO-hM4Di/ hM3Dq) to obtain its expression in the serotonergic neurons (Urban et al, 2016;Fernandez et al, 2017;Singh et al, 2017). For example, it was found that serotonergic projections from the median raphe are essential for regulating the memory of objects and the synaptic plasticity of the hippocampus (Fernandez et al, 2017).…”
Section: Optogenetic and Chemogenetic Approachesmentioning
confidence: 99%
“…Numerous studies using chemogenetic approaches were conducted to perceive the functions of serotonergic neurons and their projections. In such experiments mice of the Sert-Cre line are injected with adeno-associated viruses containing the sequence hM4Di or hM3Dq (AAV-hSyn-DIO-hM4Di/ hM3Dq) to obtain its expression in the serotonergic neurons (Urban et al, 2016;Fernandez et al, 2017;Singh et al, 2017). For example, it was found that serotonergic projections from the median raphe are essential for regulating the memory of objects and the synaptic plasticity of the hippocampus (Fernandez et al, 2017).…”
Section: Optogenetic and Chemogenetic Approachesmentioning
confidence: 99%
“…In particular the EP3Rs of the preoptic hypothalamus have been found to be responsible for signaling inflammatory fever (Lazarus et al, 2007). The EP3Rs also play a role in signaling PGE2 mediated hyperalgesia and in the affective component of pain (Minami et al, 2001;Singh et al, 2017). EP4Rs are Gs-coupled which are widely expressed throughout the brain of rodents.…”
Section: Prostaglandin E2 Synthesis and Receptorsmentioning
confidence: 99%
“…PGE 2 formed in brain venules during systemic inflammation passes the blood–brain barrier and disinhibits neurons in the median preoptic nucleolus to generate fever . COX‐2‐derived prostanoids also play a role in other central responses to systemic inflammation, such as sleepiness and anorexia, and COX‐2 expressed in the brain may modulate the affective component of pain . Indeed, as a growing body of evidence suggests that inflammatory processes play a role in affective disorders, COX‐2 products have also been implicated in anxiety and major depression .…”
Section: Cyclooxygenases and Prostanoidsmentioning
confidence: 99%